Elastic stable intramedullary nailing of femoral shaft fractures in children: Particularities and results at Sylvanus Olympio teaching hospital of Lomé, Togo - Akakpo-Numado Gamedzi Komlatsè; Boume Missoki Azanledji; Sakiye Kodjo Abossisso; Mihluedo-Agbolan Komlan Anani; Gnassingbe Komla; Tekou Hubert (Wolters Kluwer Medknow Publications, 2014)
Introduction: The elastic stable intramedullary nailing (ESIN) presently seems the best technique in the surgical treatment of femoral shaft fractures (FSF) in >6-year-old children. We hereby report technical difficulties and therapeutic results after our first 8 years of experience. Patients and Methods: It's a retrospective study over a period of 8 years from January 2005 to December 2012 in the Paediatric Surgery Department of Sylvanus Olympio Teaching Hospital of Lomé. Indications, technical particularities and results were studied. Results: There were 32 patients, 17 were boys and 15 were girls, with a mean age of 11 years old. The mean time to surgery was 21 days (range: 14 and 51 days). A callus was always removed before reduction. The osteosynthesis was stable in 22 cases, but in 10 others, it had been completed with a cast immobilisation. The operation needed a blood transfusion in 18 cases. With a mean follow-up of 3.5 years, the results were excellent in 29 patients (90.63%) and good in 3 patients (9.37%). Conclusion: Although undertaking an ESIN can be difficult, due to the lack of adequate equipment the procedure produces satisfactory outcome.